Clinical features of uterine sarcomas presenting mainly with uterine masses: a retrospective study - Menghan Zhu; Shouzhen Chen (BMC Women's Health, 2023)
Abstract Background Uterine sarcomas are uncommon mesenchymal tumors of the uterus. The clinical problem is that the features of uterine sarcomas can sometimes mimic uterine fibroids. This study aims to investigate the clinical characteristics of patients with uterine sarcomas who were preoperative presenting mainly with uterine masses. Methods A retrospective analysis of patients who underwent gynecological surgery for uterine sarcomas at the Obstetrics & Gynecology Hospital of Fudan University, between January 2016 and December 2021. Results Over the 5-year period, 277 patients were final diagnosed of uterine sarcomas. A total of 162 patients were preoperatively diagnosed as uterine fibroids for surgical treatment, the majority of whom were diagnosed of uterine leiomyosarcoma (uLMS) (49/162) and low-grade endometrial stromal sarcoma (LG-ESS) (100/162). Ninety people underwent total hysterectomy and bilateral salpingo-oophorectomy (TH + BSO), while 72 underwent myomectomy followed by supplemental TH + BSO. The group with direct hysterectomy had a higher average age than the group with prior myomectomy (47.20 ± 8.94 vs. 40.86 ± 5.88, p < 0.001). Among patients preoperatively diagnosed as uterine fibroids, patients with uLMS had a higher proportion of previous myomectomy (26.53% vs. 5.00%, p < 0.001), a larger uterine mass diameter on ultrasound (8.38 ± 3.39 cm vs. 6.41 ± 1.92 cm, p < 0.001), and richer hypervascularity (34.69% vs. 18%, p = 0.024) compared with LG-ESS. Conclusions Analysis of our data showed that a large proportion of uterine sarcomas, especially uLMS and LG-ESS, present mainly with uterine masses. Ultrasound features including a large uterine mass diameter and rich hypervascularity, and with a history of myomectomy may alert clinicians in suspicion of uLMS when compared with LG-ESS.